Clima laboral y su relación con el desempeño de los trabajadores nombrados del Gobierno Regional de La Libertad – Sede Central 2017 - Leon Ruiz, Maria Esther (2019)
ABSTRACT This research was developed with the general objective of analyzing the labor climate and the performance of the appointed workers of the Regional Government of Liberty - Headquarters 2017. The purpose is to establish the relationship between the labor climate and the work performance of the workers named in the Regional Government of Liberty - Headquarters 2017 framed within the reform and modernization of the State. The type of study is non-experimental, the design is causal correlational transectional or transversal. The population is made up of 221 appointed workers, from the Regional Government of La Libertad - Headquarters 2017, of which a sample of 86 appointed workers was considered. The applied research methods were deductive, inductive and analytical. Two reliable and duly validated questionnaires were used as instruments for data collection of the variables under study and the information was processed through statistical software for social sciences (SPSS v. 23). The results obtained are presented in tables and statistical figures, which have allowed to conclude that between the variable Labor Climate and the job performance of the appointed workers of the Regional Government of La Libertad - Headquarters, 2017, if there is a direct correlation or positive highly significant because the Spearman's Rho correlation coefficient is ,902. The level of Labor Climate in the Regional Government of Liberty - Headquarters 2017 is predominantly Medium Low. The level of job performance of the Regional Government of Liberty - Headquarters, 2017, is also predominantly Medium Low, It is recommended to arrange the execution of training programs on the vision, mission, goals and objectives of the Regional Government of La Libertad that contribute to improve the work performance of workers.